A Holistic Approach to Soccer Training: Combining Speed Endurance Training and Technical Drills - Prasetya, Febry Noeh Cahya; Phanpheng, Yanyong (JSES : Journal of Sport and Exercise Science, 2025)
Purpose: The use of combination training models is becoming increasingly popular in soccer coaching. While many combination training models focus on physical and tactical aspects, there is still a lack of integration with technical training. This study aims to analyze the effect of combining speed endurance training (SET) and technical drills on the aerobic capacity of university soccer players. Materials and Methods: Nineteen male university soccer players, randomly selected from a population of 82 players, participated in this study. The sample characteristics included an average age of 20.21 ± 0.92 years, height of 170.74 ± 4.52 cm, weight of 62.37 ± 6.65 kg, body mass index of 20.21 ± 0.92 kg/m², and soccer experience of 6.21 ± 0.85 years. This research employed a pre-experimental design with a one-group pretest-posttest. We used the paired-samples and Wilcoxon tests to analyze pretest and posttest differences, with normality assessed using the Shapiro-Wilk test. The study evaluated speed performance, total distance, and VO2max. Result: Results showed significant differences in pretest and posttest mean values for speed, total distance, and VO2max (p < 0.05). Speed performance increased by 0.52 ± 0.50 km/hr, total distance by 362.11 ± 247.11 meters, and VO2max by 3.06 ± 2.07 ml/kg/min. Conclusion: These findings indicate that the combination of SET and technical drills positively impacts the aerobic performance of male university soccer players.